Pengaruh Harga terhadap Keputusan Pembelian pada Ravis Catering di Surakarta - Berta Berlianda; R. Taufiq Nur Muftiyanto; Agus Suyatno (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
New businesses face their own challenges due to developments in the current business world. Business is currently experiencing a lot of progress due to the emergence of various companies in various fields, both industry and services. The research carried out by the author is a type of quantitative research. 285 Ravis customers were involved in this research. The purposive nonprobability method was used to find samples in this research. Data is provided directly to data collectors by data sources. Data obtained from questionnaires and interviews in this research were processed through the Likert data processing system. Ho is rejected and ha is accepted, according to the t test results, because the price variable is tcount 8.717 and ttable 1.66660. Based on the results of the coefficient of determination table, ho and ha are accepted.